Binding a saint. Origin stories and identity construction of divine intermediaries - Torres Calizaya, Teresa Judith (2016)
It is postulated that the popular stories about saints in the area of Tarata (Tacna) are a continuation of the Andean stories as a result of active listening of the official hagiography (exposed by the evangelizers during the conquest and colony) by the Indians. Although, the stories about saints are far from the official hagiography, the mention of elements that show the saint as a paradigm and how this went through a process of transformation and blend with the environment, in which it was settled or “decided to stay” is evident. The Saints are constituted in characters that enable and support the process of identification with the new culture; when we attribute job and geographical knowledge of the area through interaction with local authorities. Syncretism and oral constant renewal that does not erase the Andean aesthetics and performance is built.